Effects of replacing fat with Perilla seed on the characteristics of meatballs. (March 2020) - Ran, Miao; Chen, Changyong; Li, Cuiqin; He, Laping; Zeng, Xuefeng
Abstract: A portion of the fat used in the preparation of meatballs was replaced with different amounts of Perilla seeds rich in unsaturated fatty acids. Five treatments with mass percentages of 0%, 5%, 10%, 15%, and 20%, including a set of blank treatment and four groups treated with different Perilla seed contents, were performed. The effects of Perilla seed content on the proximate composition, pH, color, cooking yield, emulsion stability, texture, fatty acid composition, and sensory properties of meatballs were analyzed. The meatballs with Perilla seeds showed remarkably better properties than those without seeds. The addition of 10% ( w / w ) Perilla seeds significantly (P < 0.05) improved the texture, composition, and content of polyunsaturated fatty acids (PUFAs), dietary fiber, and protein in meatballs. Moreover, the characteristic flavor components were rich and varied, which enhanced the taste, flavor, and satiety of the meatballs. This work provided theoretical and data support for the preparation of Perilla meatballs rich in PUFAs and dietary fiber.